The screened triterpene acids from Loquat fruit by CysLTR1-immobilized column could serve as alternative anti-inflammatory agents - Tian Yang; YiFan Yan; YiYing Xu; YiLong Chen; DaLong Zhi; Yan Zhang; ChaoNi Xiao (BMC Complementary Medicine and Therapies)
Abstract Background Loquat (Eriobotrya japonica Lindl.) fruit has been used as a heath food and folk medicine for preventing and treating the respiratory tract inflammation diseases, however, the active compounds responsible for anti-inflammation effects remain unclear. Methods Cysteinyl leukotriene receptor-1 (CysLTR1) has become an important target protein for developing therapeutics to manage the inflammation-associated diseases. Herein, a rapid approach was established by immobilizing CysLTR1 onto microspheres for the column packing, and it was applied in screening the active compounds from Loquat fruit. Results The screened compounds targeting CysLTR1 were identified as corosolic acid, ursolic acid and oleanolic acid in combination with Mass Spectrum. The high-dose combination of the three ones exhibited the stronger anti-inflammatory activity than triterpene acid alone and the Loquat extract, which can significantly decrease the counts of inflammatory cells and inhibit the production of pro-inflammatory mediators as well as increase the secretion of anti-inflammatory mediator in the LPS-inflamed mice. It was proved that three triterpene acids exhibited anti-inflammatory activities by the attenuation of CysLTR1 expression. Conclusions Our results indicated that CysLTR1-immobilized column was a rapid and effective tool to seek out the target-specific components from herbal extract, and the screened triterpene acids could serve as alternative anti-inflammatory agents to Loquat fruit.